2021
DOI: 10.3390/su132011370
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Frequency of Nature Dose: How Continuous and Regular Forest Walking Improves Nature Relatedness, Restorativeness, and Learning Engagement in College Students

Abstract: Forest is a natural resource that provides natural walking as a popular leisure activity for urban residents. From the perspective of “dose of nature,” continuous contact with natural environments and engagement in natural activities can gradually promote positive health benefits. This study aims to explore the “cumulative frequency of nature dose” through regular forest walking. Ten college students were recruited to walk once a week for 30 min in the campus forest. Eight weeks of forest walking experiences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…One unexpected finding was that there was no significant improvement of nature relatedness for participants in nature group after seven consecutive walking. This finding is partly consistent with one study, which has shown that the degree of nature relatedness not significantly improved after walking for four times, however, it significantly increased when participants walked for eight weeks 60 . That study implied that longer the forest walking, the greater levels of nature relatedness that participants may perceive.…”
Section: Discussionsupporting
confidence: 91%
“…One unexpected finding was that there was no significant improvement of nature relatedness for participants in nature group after seven consecutive walking. This finding is partly consistent with one study, which has shown that the degree of nature relatedness not significantly improved after walking for four times, however, it significantly increased when participants walked for eight weeks 60 . That study implied that longer the forest walking, the greater levels of nature relatedness that participants may perceive.…”
Section: Discussionsupporting
confidence: 91%
“…Practicing mindful observation and further enhancing dispositional mindful observation could be helpful before engaging with or being exposed to the natural environment. Also, the result was consistent with the dose theory [42,43] and the existing experimental studies [30,31]. As a cross-sectional study, our findings supported that the effect of mindful observation on the relationship between contact with nature and mental health could be accumulated from a state to a disposition and affect mental health both in the short-term and long-term.…”
Section: Main Findingssupporting
confidence: 91%
“…It has been found that individuals with a stronger connection to nature were less likely to be depressed, stressed, and anxious 40 , and tend to be happier, have higher attention spans, encounter less cognitive fatigue 41 , have an overall improved health, attitudes, and behaviours 42 , have lower state and trait cognitive anxiety 43 . Regarding youth, university students benefit from regular walks in nature on mental health, learning engagement, attention recovery, reflection experiences, and nature connectedness 44 . Nature-based interventions have increased happiness and connectedness among university students 45 .…”
Section: Introductionmentioning
confidence: 99%